Features of Stress State of Germanium Nanocrystals in SiOx Matrix - Kuryliuk, V V; Korotchenkov, O A; Tsybrii, Z F; Nikolenko, A S; Strelchuk, V V (Journal of Nano- and Electronic Physics, 2015)
Features of mechanical stress in germanium nanocrystals synthesised in amorphous SiOx matrix with SixNy buffer layer were studied by means of Fourier transform infrared absorption spectroscopy, Raman scattering and computer modeling. It was found that the germanium nanocrystals are under significant compressive stress with a magnitude of up to 2.9 GPa. Such a high strain value can be explained by a partial penetration of the nanocrystals in the silicon substrate. In this case the principal source of mechanical stress is the lattice mismatch between silicon and germanium.